The Quality of Audit Cervices: Dreams and Illusions - О. Yu. Redko (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
A review of quality in the context of audit services leads to the conclusion that if the services fully conform to the customer’s expectations, these services are quality ones. The quality of audit services is analyzed from the perspective of the Law of Ukraine “Audit of Financial Reporting and Audit Activities” from 21.12.2017. Analysis of factors differentiating customer expectations of the results of audit services allow for the conclusion that because quality requirements set by various auditors for the same audit service may differ, a single set of quality criteria cannot be elaborated.   It is argued that given the specifics involved in auditor services, their quality assessment would be a difficult matter. The argument is supported by extracts from the abovementioned Law. It is concluded that the Law, not containing a definition of the quality of audit services, puts emphasis on formal professional characteristics in the assessment of professional capacities of audit firms rather than results of their work.It is shown that because the Law has no provisions about the auditor’s right to own professional opinion, arbitrariness in the quality assessment of audit is legally fixed in Ukraine, opening doors for corruption.Quality criteria for audit services are proposed, grouped by basic quality criteria and supplementary quality criteria. Factors preventing from fixation of price for audit services and from acceptance of price as a quality criterion are given. The reason why the criterion of staff number in audit firms cannot be used for quality assessment purpose is explained. The conditions that need to be put in place to have the quality of audit in Ukraine conform to social demands are highlighted.